Psychological and physical abuse of indiginous women (Research, Society and Development, 2024)
This study addresses the psychological and physical abuse attributed to Indigenous women, caused by disrespectful conduct in hospital/medical care settings in this target audience. Its objective is to discuss the psychological and physical abuse of indigenous women. The research methodology for this study was an integrative review of literary works from the last five years, limited to the period from January 2019 to August 2024, which occurred through specific health and multidisciplinary databases, such as PubMed, Lilacs, Medline, SciELO, and others. For the other delimitations of data collection and analysis, eligibility criteria were applied, to be detailed in the methodological section of this article. The results obtained in the review denote a scarcity of content that delimits the problem in the audience of Indigenous women proposed in this study. The wide range of articles found translates psychological and physical abuse in the most variable contextualization, but without addressing Indigenous women or descendants. Finally, it is possible to observe that little emphasis was placed on identifying the factors and interventions against disrespect and abuse against the population addressed in the country were carried out, making it necessary to assign new social and governmental implementations that act directly on the rights of Indigenous women who have suffered or suffer abuse within public health care settings.